EFFECTS OF ADDITIONAL KINESIOLOGICAL OPERATORS ON THE SPEED PROPERTIES OF ATHLETES IN SPORTS OF MONOSTRUCURAL AND POLYSTRUCTURAL TYPE - Mladen Pavlinović; Eldar Goletić; Sanjin Hodžić; Dragiša Jovanović; Lejla Goletić (Sport Scientific And Practical Aspects, 2025)
The research was conducted on a sample of athletes aged 13-15 from BiH, namely 60 athletes and 60 karate players. The participants were divided into groups consisting of 30 athletes and karate athletes. Experimental groups of athletes, in addition to regular training operators, had additional operators, while the control group of athletes and the control group of karate players performed the training process by practicing regular kinesiological operators. A set of nine variables was used to evaluate the speed properties of the investigated sample of athletes. The assessment of segmental velocity was carried out with three common variables, speed in athletes with three variables characteristic of speed assessment for athletes and speed in karate players with three variables specific to the assessment of speed in karate players. Therefore, the main objective of this research is to determine the effects of the application of additional training operators on the rapid properties of athletes in sports of monostructural and polystructural type. The program of additional kinesiology operators was implemented within five training units during the weekly microcycle. The treated speed properties of athletes in a period of six months, which in addition to the basic program include the program of additional training operators, progressed significantly faster and better within the experimental treatment. Also, positive effects were achieved by applying the basic program in the control sample, but on a somewhat smaller scale. From a kinesiological- methodical point of view, the applied experimental treatment indicates the fact that it has largely contributed to positive effects in the experimental group of athletes in relation to the control group. It is also evident that in both groups of karate players there are positive changes in velocity properties. However, the experimental group sees a significantly better transformation of certain anthropological features compared to the control group. These facts suggest that the application of additional kinesiological operators in the experimental group produced greater effects on the development of rapid properties in the experimental karate team compared to the control group.